Association of Gonadotropin-Releasing Hormone Therapies With Venous Thromboembolic Events in Patients With Prostate Cancer: A National Cohort Study - Hong, Chon-Seng; Chen, Yi-Chen; Ho, Chung-Han; Hsieh, Kun-Lin; Chen, Michael; Shih, Jhih-Yuan; Chiang, Chun-Yen; Chen, Zhih-Cherng; Chang, Wei-Ting (Frontiers in Cardiovascular Medicine, 2022)
Although androgen deprivation therapy (ADT) has been proposed to be associated with a higher risk of venous thromboembolisms (VTEs), whether gonadotropin-releasing hormones (GnRHs), such as both agonists and antagonists, are also associated with VTEs remain unclear. Using the Taiwan Cancer Registry (TCR) linked with the National Health Insurance Research Database, we identified patients diagnosed with prostate cancer from 2008 to 2015. Patients who received GnRH were 1:1 propensity score matched with non-GnRH users by age and cancer stage at diagnosis and clinical stage. Cox regression analysis was applied to estimate the incidences of VTEs with death as a competing event at the 5-year follow-up. The VTE incidence among GnRH users was 1.13% compared with 0.98% among non-users. After adjusting with potential confounding factors, the risk of VTEs showed borderline statistical significance among GnRH users and non-users. Notably, in the subgroup analysis among patients receiving GnRH therapy, those younger than 70 years old or at an earlier stage (stage I/II) were at a higher risk of VTEs. Different from previous studies, our findings highlighted critical concerns regarding the cardiac safety of GnRH therapies in prostate cancer patients at a relatively younger age or at an earlier stage.